Harmonization of Sundanese Culture with Traditional Musical Instruments in West Java - Dini Alfiani; Mila Deskia; Nabila Tri; Tin Rustini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Indonesia as an archipelagic country with diverse tribes, races, cultures, and languages faces challenges in preserving the sustainability of its traditional culture, including traditional musical instruments that are important in various regions, such as West Java. Traditional Sundanese musical instruments, such as angklung, gamelan, kecapi, and kendang, have important philosophical and spiritual values for the Sundanese people. However, knowledge and development of traditional musical instruments is still lacking among the Indonesian people, especially the younger generation. Conservation efforts involve various programs and initiatives from the government, related institutions, and local communities, but the challenges of globalization and modernization require more intensive efforts to promote, preserve, and develop traditional Sundanese musical instruments to the younger generation and the outside world.